Genomic variation landscape of the human gut microbiome - Schloißnig, Siegfried; Arumugam, Manimozhiyan; Sunagawa, Shinichi; Mitreva, Makedonka; Tap, Julien; Zhu, Ana; Waller, Alison; Mende, Daniel R.; Kultima, Jens Roat; Martin, John; Kota, Karthik; Sunyaev, Shamil R.; et al. (Nature, 2013)
Whereas large-scale efforts have rapidly advanced the understanding and practical impact of human genomic variation, the practical impact of variation is largely unexplored in the human microbiome. We therefore developed a framework for metagenomic variation analysis and applied it to 252 faecal metagenomes of 207 individuals from Europe and North America. Using 7.4 billion reads aligned to 101 reference species, we detected 10.3 million single nucleotide polymorphisms (SNPs), 107,991 short insertions/deletions, and 1,051 structural variants. The average ratio of non-synonymous to synonymous polymorphism rates of 0.11 was more variable between gut microbial species than across human hosts. Subjects sampled at varying time intervals exhibited individuality and temporal stability of SNP variation patterns, despite considerable composition changes of their gut microbiota. This indicates that individual-specific strains are not easily replaced and that an individual might have a unique metagenomic genotype, which may be exploitable for personalized diet or drug intake.